Direct-fed microbials optimize ruminal fermentation, microbial ecosystem and milk quality to enhance the lactation performance of Sanhe dairy cows - Aoyu Jiang; Zixin Liu; Ziyan Yang; Shizhe Zhang; Jian Wu; Chuanshe Zhou; Zhiliang Tan (Animal Microbiome)
Abstract The growing global population and rising living standards require a higher supply of dairy products. Dairy cows are the most important source of milk production, with billions of microorganisms present in the rumen. This study aims to assess the impact of direct-fed microbials (DFMs) containing Lentilactobacillus buchneri, Bifidobacterium longum, and Pediococcus pentosaceus on rumen fermentation parameters, rumen microbial composition, and lactation performance in dairy cows. Twelve Sanhe dairy cows with similar physical condition, parity and lactation were randomly divided into two groups of six cows each. The control group was fed a basal diet and the treatment group was fed a basal diet plus DFMs (20 g/day) for the experimental period of 60 days. Rumen fluid, blood, milk, and feces were collected from cows for detection and analysis. DFMs enhanced the apparent total tract digestibility of crude protein and neutral detergent fiber (P < 0.05), and elevated milk protein rate of Sanhe dairy cows (P < 0.05). In the ruminal environment, supplementation of DFMs promoted the production of microbial proteins, acetate and total volatile fatty acids (P < 0.05). High-throughput sequencing analysis of rumen microorganisms revealed that relative abundance of DFMs were elevated in the treatment group, and DFMs enhanced the relative abundance of Prevotella, Pseudoclostridium and Faecalibacterium in the rumen (P < 0.05). In predictive analysis of microbial functional genes, the treatment group was enriched with more genes encoding hemicellulose-degrading enzymes such as GH10, GH30, and GH67, while the relative abundance of genes encoding enzymes that metabolize ammonia was increased. In addition, the analysis of rumen bacteriophages showed that DFMs significantly increased the relative abundance of bacteriophages infecting Prevotella in the rumen. Overall, DFMs enhanced the degradation of protein and carbohydrate in Sanhe dairy cows. There was a positive correlation with the relative abundance of Prevotella, which may provide substant amino acids and energy for milk protein synthesis, improving the lactation performance of Sanhe dairy cows.